Video-Based Promotion Strategy to Increase the Economic Value of Local Coffee “Kejapa” in Tigawasa Village, Buleleng - Wau, Rendi Syaputra; Widiastini, Ni Made Ary; Nugraha, I Gede Putra (Badan Riset dan Inovasi Daerah Provinsi Bali, 2026)
Purpose: This study aims to analyze the role of video-based promotional strategies in increasing the economic value of Kejapa Coffee, a local product of Tigawasa Village, Buleleng, Bali. Research methods: This study uses a descriptive qualitative approach. The data collecting techniques used include field observation, video content documentation, and interviews with business owners. Promotional media were analyzed through Instagram, WhatsApp Business, and the use of barcodes on product packaging. The video production process was carried out using a digital camera and video editing applications. Results and discussion: The results show that video-based promotions increase product visibility, strengthen quality perceptions, and encourage consumer interaction. The economic impact is evident in increased demand, market expansion, and new business opportunities based on local coffee. Implication: Video promotional strategies can be an effective instrument in strengthening the local economy, increasing the competitiveness of MSMEs, and developing village potential based on superior products and cultural narratives.